Cardiovascular risk rate in hypertensive patients attended in primary health care units: the influence of pharmaceutical care - Paulo Yuri Milen Firmino; Tainá Osterno Vasconcelos; Caroline Carneiro Ferreira; Larissa Mendonça Moreira; Nirla Rodrigues Romero; Lilian Araújo Dias; Maria Goretti Rodrigues de Queiroz; Marcos Venícios de Oliveira Lopes; Marta Maria de França Fonteles (Universidade de São Paulo, 2015)
Cardiovascular complications are relevant due to their frequency and severity on the hypertension scenario. Studies refer Pharmaceutical Care (PC) as capable of decreasing cardiovascular risk rate (%CVR) on hypertensive patients. This study aimed to investigate, through a randomized clinical assay, the influence of PC service on the %CVR of hypertensive patients assisted in a health primary care unit from Fortaleza-Ceará. Two study groups were formed: i. Intervention Group (IG), which received orientation about taking medicines, actions aiming to prevent/solve medicine interactions and adverse effects and non-pharmacological interventions for 9 months and, ii. Control Group (CG), which received traditional assistance of the unit and was monitored during the same period. It was observed a statistically significant reduction on %CVR (10.76 to 7.86; p=0.04) and systolic blood pressure levels (SBP) (137.69 to 131.54; p<0.01) in the IG, while, in the CG, there was no significant alteration. 151 Drug Related Problem (DRP) were identified and it was realized 124 pharmaceutical interventions, with 89.2% of them resulting on solution/prevention of the problem. Our findings indicated that the inclusion of the PC service in the hypertensive health assistance was more effective at the %CVR and the SBP reduction in comparison to the traditional assistance offered.